An Examination into the Validity of Secondary School Entrance Scores in Predicting the Academic Success of Secondary Aged Students - Martin Timothy Hall (Arizona State University, 2015)
The Barbados Secondary School Entrance Examination (BSSEE) is used to allocate students to secondary schools in Barbados. However, this means of allocation has always been contentious. Therefore the aim of this study was to establish the predictive validity of the BSSEE in relation to the Caribbean Secondary Education Certificate (CSEC). Academic achievement was measured using students performances on the BSSEE and CSEC. The sample included 252 students across Barbados (130 males, 122 females). The results showed that the BSSEE accounted for 29% of the variance for this sample. Additionally, the means of female students were higher on both the BSSEE and CSEC, but only a statistically significant difference was obtained on the BSEEE. The BSSEE should be used in conjunction with other assessment scores as a fairer means to allocate students. Furthermore, the BSSEE should be used as a diagnostic tool for remediation.